It's the fear of the unknown: Transition from higher education for young autistic adults. (August 2019) - Vincent, Jonathan
More young people with a diagnosis of autism are enrolling and successfully completing higher education courses than ever before and this is set to increase; however, while there is a burgeoning body of literature surrounding the transition into this stage of education, there is a paucity of research that investigates the transition as this population exit higher education. This exploratory qualitative study is one of the first to identify the specific experiences of young autistic adults making this transition, drawing on semi-structured interviews with 21 students and recent graduates. Findings indicate that transition out of higher education is challenging on both practical and psychological levels, manifested by feelings of anxiety and loss. However, there is also evidence that the same phenomenon can also be understood as a positive departure with important implications for identity development. Findings are discussed in relation to future research and implications for practice in higher education institutions.